Recognizing Heat Stress in Dairy Cows - Izabella M. Toledo; Geoffrey E. Dahl (EDIS)
In persistent hot, sunny and humid conditions, cows can become overheated and may not produce as well, or may experience health issues. This two-page fact sheet written by Izabelle Toledo and Geoffrey Dahl and published by the UF/IFAS Department of Animal Sciences lists the signs of heat stress in dairy cows. https://edis.ifas.ufl.edu/an356